Replication Data for: Predicting the future climatic suitability for cocoa farming of the leading producer countries, Ghana and Ivory Coast. - Läderach, Peter R.D.; Martínez Valle, Armando Isaac; Schroth, Götz; Castro, N. (2014)
Data for current and future suitability for cocoa farming of the world"s leading producer countries, Ghana and Ivory Coast. Based on species distribution modelling: MaxEnt.